Literasi Investasi sebagai Upaya untuk Meningkatkan Perilaku Sadar Berinvestasi pada Kelompok Investor Pemula di Kudus - Izza Ashsifa; Naila Rizki Salisa; Ulva Rizky Mulyani (Muria Jurnal Layanan Masyarakat, 2022)
This proposed community service program is designed to provide solutions and assist novice investors in making investments. The basis for proposing this service is the existence of problems, including the limited ability of human resources to obtain investment information and how to manage it, lack of financial literacy, do not have long enough financial goals, and do not have special capital only for investment, experiencing fear to do investment, not confident, and afraid of losing. The activities that will be carried out in this service are to provide investment literacy as an effort to increase investment awareness behavior. The objectives to be achieved are: 1) increasing public awareness of the importance of investing 2) increasing the understanding of novice investors about investment instruments 3) beginner investors can choose the right type of investment and 4) beginner investors can apply good investment strategies. The approach offered in the realization of this service is a mentoring model through outreach activities that focus on investment literacy, capital markets, risks, and returns on investment.